Financial Behavior and Knowledge, and Parents’ Education and Revenue on Management Students’ Financial Behavior - Sari, Meyristiana; Santoso, Rahmat Agus; Handayani, Anita; Reviandani, Wasti (Interdisciplinary Social Studies, 2022)
Financial behavior is the study of how psychological phenomena affect financial behavior. This financial behavior can be influenced by several factors including financial attitude, financial knowledge, and income. However, there are other factors that can influence financial behavior such as parental education. This research aims to find out the influence of Financial Attitudes, Financial Knowledge, Parental  Education, and, Parental  Income on Financial  Behavior in Management Students of the Muhammadiyah University of Gresik. The research method uses quantitative research methods with a sample of 159 respondents.  The data obtained is analyzed with multiple linear regression analysis techniques using the SPSS 25 program.  The results showed that financial attitudes have a positive effect on financial behavior, financial knowledge has a positive effect on attitude-behavior, parental education has a positive effect on behavior and parental income positively affects financial behavior.